The effects of duration of ultrasonication on the morphology and structural properties of Ni-doped hydroxyapatite structure - Ateş, Tankut; Keser, Serhat; Bulut, Niyazi; Kaygılı, Omer (Niyazi BULUT, 2022)
This work aims to explain the effects of sonication periods, ranging from 0 to 4 h with a step of 1 h, on the morphology and structural properties of Ni-doped hydroxyapatites at a constant amount of 0.4 at.%. The lattice parameters, crystallinity, and crystallite size were affected by the sonication time. Among the sonicated samples, it was observed that the increasing sonication period reduced the c/a ratio. It was also found that the morphology was affected by the ultrasonication duration.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri